Production function estimations and policy implications - Khreisat, Mohammad Abdallah, author; Cutler, Harvey, advisor; Mushinski, David, committee member; Shields, Martin, committee member; Davies, Stephen, committee member (Colorado State University. Libraries, 2011)
The main purpose of the dissertation is to provide the decision makers in local governments in Colorado with a information regarding the economic characteristics of industries and firms they need to attract to their regions to mitigate the inverse impacts of job loss, and local government revenue decreases during economic down turns. The dissertation estimates four different production functions classified in two groups; homogeneous functions, and non-homogeneous functions. The estimation is held at the industry level using firm level data for six major counties in Colorado. This is the first empirical study that explores the importance of land in the production process, in addition to the primary inputs of capital stock and labor. The study also determines the production function that best fits the data structure instead of other studies which assume in priori the type of production function. In addition, the study will explore the returns to scale and elasticity of substitutions for the three input variables (land, labor, and capital) at the industry and firm levels. Furthermore, the dissertation explores the convergence of total factor productivity within industry and among counties, and within county and among the different industries in the same county. The main findings of the study are: (i) local governments have to attract the industries or firms with low elasticity of substitutions between labor and capital from one side; and industries or firms with low complementarity between land and labor, and capital and land; (ii) land is an important input variable in the production process, especially in Denver County; (iii) local government has to attract firms with increasing returns to scale because of their positive impact on employment, economic growth, local government revenues, and competitiveness outside the county; (iv) local governments have to encourage firms with high k/l ratio accompanied with low elasticity of substitutions; and (v) the negative relation between total factor productivity and partial scale elasticity, leads to the conclusion that the industries or firms either substitute TFP with RTS or firms with high RTS delay applying advanced technology.
Keywords: elasticity of substitution or complementarity; homogeneous production functions; model fitness; nonhomogeneous production functions; total factor productivity; varies returns to scale